Diversity of Lichens in Yala Rajabhat University: Air Pollution Bioindicator - รุ่งพิทักษ์ไชย, ฉันทนา; รักขพันธ์, ลักขณา; ทองไชย, อลภา; แก้วอ่อน, สายใจ; พังสุบรรณ, ศศิธร (YRU Journal of Science and Technology, 2018)
The research of lichens in Yala Rajabhat University, Muang Yala district, Yala province during October 2014 to September 2015 was aimed to study the biodiversity, morphological characteristics and habitat of lichens in order to preliminarily assess the air pollution in Yala Rajabhat University. The lichen samples were randomly taken from bark of trees. Then the species of lichens were identified and grouped on the tolerance against air pollution. A total number of 150 samples were divided to two groups and identified to 14 family, 26 genus and 55 species. Thirteen families, 23 genus, 46 species of crustose were found as the most tolerance to air pollution. The dominant family of crustose was Graphidaceae. One families, 3 genus, 9 species of foliose were found as the moderate tolerance to air pollution. The families of fuliose was Phyciaceae. These data were then used to assess the air quality. Overall, the air quality in Yala Rajabhat university was good since three groups of lichens including the sensitive (Rinodina sp.), the moderate tolerant (Trypethelium tropicum) and the high tolerant (Trypethelium eluteriae) lichens were found in the same area.